Do South Indian newborn babies have higher fat percentage for a given birth weight?. (May 2016) - KV, Radha Krishna; Hemalatha, Rajkumar; Mamidi, Raja Sriswan; JJ, Babu Geddam; Balakrishna, N.
Abstract: Background: India is experiencing rapidly escalating epidemics of diabetes and cardiovascular disease. High fat percent in Indian adults may have its origins at birth (Fetal origin hypothesis). Conflicting evidence from India have shown increased or similar fat mass in Indian newborn babies compared to western countries. Aim: To compare body composition of term infants with data from similar studies in India and developed countries. Study design: Cross-sectional study in newborn infants at the antenatal ward of a tertiary care hospital in South India. Subjects: 626 mothers and their newborn babies. Outcome measures. Maternal body weight and height, baby weight, length, head circumference, skin folds at three sites. Body fat, arm muscle area and arm muscle index were calculated based on known methods. Results: Mean (SD) birth weight of newborn babies was 2.80 (0.37) kg and 43% of them were small for gestational age. Birth weight was significantly related to subscapular (r = 0.445; p < 0.001) and triceps (r = 0.567; p < 0.001) skin fold thickness. Mean (CI) Subscapular skin fold thickness and total body fat % was 3.81 mm (3.74–3.97) and 10.5% (10.2–10.8). Mean total body fat % for small for gestational age (SGA) (9.57%) was significantly lower than appropriate for gestational age (AGA) babies (11.7%). Conclusions: The mean body fat percent in AGA infants was similar to that of studies reported on term infants of developed countries, suggesting that South Indian babies may accumulate similar fat mass with increasing birth weight and gestational age. Highlights: India is experiencing rapidly escalating epidemics of diabetes and cardiovascular disease. Our study shows that the fat mass of Indian newborn babies is similar to data from western countries. High fat percent in Indian adults may not have its origins at birth.